This study aims to analyse the organizational culture based on Islamic values and identify the challenges and strategies for its development. The problem addressed is the need to strengthen and optimize the implementation of Islamic-based organizational culture in madrasahs to improve the performance of educators and create a harmonious work environment. This research utilizes a qualitative descriptive method by case-study design through interviews, observations, and document analysis to provide - Tri Oktaviani, Eka; Nugraha, Mulyawan Safwandy; Azmy, Muhammad Naufal Tsabitul (at-Tahsin, 2026)
This study aims to analyse the organizational culture based on Islamic values and identify the challenges and strategies for its development. The problem addressed is the need to strengthen and optimize the implementation of Islamic-based organizational culture in madrasahs to improve the performance of educators and create a harmonious work environment. This research utilizes a qualitative descriptive method by case-study design through interviews, observations, and document analysis to provide a comprehensive picture of the institution’s values, work practices, communication patterns, and policies. The locus of this research is at at MTs As-Sakinah Cirinu Garut. The research findings reveal that the organizational culture in this madrasah is founded on Islamic values such as Shidiq, Amanah, Istiqamah, Tabligh, and Fathanah, which are reflected in practices of transparency, discipline, cooperation, and teacher professionalism. However, challenges in implementing Islamic culture include resistance to change, differing interpretations of values among teachers, and ineffective internal communication. The study also indicates that the organizational culture has a positive influence on educator performance and the harmonization of the work environment. It was found that the integration of Islamic values into the school culture fosters a supportive atmosphere for collaboration and growth among the staff. Furthermore, there is a clear connection between the values promoted by the school and improved student outcomes, demonstrating the significance of a strong cultural foundation in education. Future research is recommended to explore the involvement of parents and the broader community as supporting factors in strengthening Islamic organizational culture in madrasah.